2002
DOI: 10.1177/000456320203900604
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Maternal Serum Biochemical Markers of Trisomy 21 across the First and Second Trimester of Pregnancy

Abstract: There is significant temporal variation in mean log10MoM values for the screening markers investigated. Screening algorithms, modified to take account of this variation, should allow more accurate gestation-specific risks to be calculated in individual pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 29 publications
4
22
1
Order By: Relevance
“…The variation in SD of log 10 (NT MoM) with gestational age and the declining median NT MoM in trisomy 21 pregnancies clearly all add further evidence to the inappropriateness of the MoM approach, which ultimately leads to women being given inaccurate patient‐specific risks. Such temporal variation of marker MoMs has also been observed with first‐ and second‐trimester biochemical markers, but in general the distributions in the log 10 domain are Gaussian16. Nevertheless, it was suggested that to produce accurate patient‐specific risks the algorithms should no longer use the constant median separation model but they should be modified to a variable separation model in which each week of gestation has its own specific model parameters producing more accurate individual patient‐specific risks17.…”
Section: Discussionmentioning
confidence: 86%
“…The variation in SD of log 10 (NT MoM) with gestational age and the declining median NT MoM in trisomy 21 pregnancies clearly all add further evidence to the inappropriateness of the MoM approach, which ultimately leads to women being given inaccurate patient‐specific risks. Such temporal variation of marker MoMs has also been observed with first‐ and second‐trimester biochemical markers, but in general the distributions in the log 10 domain are Gaussian16. Nevertheless, it was suggested that to produce accurate patient‐specific risks the algorithms should no longer use the constant median separation model but they should be modified to a variable separation model in which each week of gestation has its own specific model parameters producing more accurate individual patient‐specific risks17.…”
Section: Discussionmentioning
confidence: 86%
“…A similar pattern was shown for free β‐hCG in the first trimester when levels increased from 1.75 at 11 weeks to 2.25 at 13 weeks and for PAPP‐A, the levels increased from 0.44 at 11 weeks to 0.69 at 13 weeks [Spencer et al, 1999b]. In a comprehensive analysis of data from between 700 and 1,000 cases with trisomy 21 and over 100,000 unaffected pregnancies Spencer et al [2002, 2003a] have described in detail the temporal variation across the first and second trimester for the markers AFP, PAPP‐A, free β‐hCG, and total hCG. The result of this temporal variation is that the separation between normal pregnancies and those with trisomy 21 is changing all the time.…”
Section: Improving Accuracy Of Individual Risks—co‐variablesmentioning
confidence: 99%
“…The result of this temporal variation is that the separation between normal pregnancies and those with trisomy 21 is changing all the time. Using such a variable separation model prevents significant errors in individual patient‐specific risks when compared to a model where temporal change is not taken into account [Spencer et al, 2002, 2003a]. The other feature of such temporal variation is that for individual markers, there are key measuring periods.…”
Section: Improving Accuracy Of Individual Risks—co‐variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these rates can be improved by applying different first‐trimester screening strategies. Some markers are known to distinguish better between Down syndrome cases and controls, either earlier or later in the first trimester2, 3, 5, 9. Therefore, it may be appropriate to draw two separate blood samples in the first trimester and integrate these for the combined test (two‐sample combined test).…”
Section: Introductionmentioning
confidence: 99%